PERAN PENGAWASAN KANTOR IMIGRASI KELAS I JAKARTA TIMUR TERHADAP IZIN TINGGAL TKA (TENAGA KERJA ASING) - Sininta, Marganda; Astuti, Puji; Astrika, Lusia (Journal of Politic and Government Studies, 2016)
Immigration is an important part of a country to regulate a wide range of foreign nationals in and out of Indonesian territory, including East Jakarta with the number of arrivals and the presence of foreigners is increasing every year. Class I Immigration Office in East Jakarta on duty in terms of supervision residence permit TKA (Expatriates) located in East Jakarta. In government policies, adopts a selective immigration policy which is based on the principle of selective policies. Based on the system only strangers that benefit the welfare of the people of the nation and the Republic of Indonesia, which does not jeopardize the security and order and not hostile both to the people and the Republic of Indonesia which is based on Pancasila and the Constitution of 1945 (UUD 1945 ), which is allowed to enter or exit the territory of Indonesia.This type of research is descriptive qualitative analytic approach and methods used are interviews, literature, documentation, and observation. This study aims to explain how the supervisory role of the Immigration Office of the First Class of the East Jakarta residence permits of foreign workers (foreign labor) and inhibiting factors as well as support in surveillance.The results of this study are Class I Immigration Office East Jakarta has 5 methods of supervision that administrative supervision, field supervision, mapping (mapping), reports and monitoring with APOA (Foreigner Control Applications). Inhibiting factor in surveillance including the factor HR (Human Resources) and the lack of society's active role in providing information about the presence of strangers. The supporting factors in the supervision are internal factors that support the head office in the form of facilities and internal factors are the TIMPORA (Foreigner Control Team).From the research that has been done can be concluded, that there are still obstacles in the supervision of Residence Permit conducted foreign nationals. Responding to the things mentioned above, the Office of East Jakarta Immigration Class I, should continue to socialize, reinforce regulations, improve safety and maintenance procedures Residence Permit.